Sex differences in healthcare expenditures among adults with diabetes: evidence from the medical expenditure panel survey, 2002-2011 - Joni S. Williams; Kinfe Bishu; Clara E. Dismuke; Leonard E. Egede (BMC, 2017)
Abstract Background The evidence assessing differences in medical costs between men and women with diabetes living in the United States is sparse; however, evidence suggests women generally have higher healthcare expenditures compared to men. Since little is known about these differences, the aim of this study was to assess differences in out-of-pocket (OOP) and total healthcare expenditures among adults with diabetes. Methods Data were used from 20,442 adults (≥18 years of age) with diabetes from the 2002-2011 Medical Expenditure Panel Survey. Dependent variables were OOP and total direct expenditures for multiple health services (prescription, office-based, inpatient, outpatient, emergency, dental, home healthcare, and other services). The independent variable was sex. Covariates included sociodemographic characteristics, comorbid conditions, and time. Sample demographics were summarized. Mean OOP and total direct expenditures for health services by sex status were analyzed. Regression models were performed to assess incremental costs of healthcare expenditures by sex among adults with diabetes. Results Fifty-six percent of the sample was composed of women. Unadjusted mean OOP costs were higher for women for prescriptions ($1177; 95% CI $1117-$1237 vs. $959; 95% CI $918-$1000; p < 0.001) compared to men. Unadjusted mean total direct expenditures were also higher for women for prescriptions ($3797; 95% CI $3660-$3934 vs. $3334; 95% CI $3208-$3460; p < 0.001) and home healthcare ($752; 95% CI $646-$858 vs. $397; 95% CI $332-$462; p < 0.001). When adjusting for covariates, higher OOP and total direct costs persisted for women for prescription services (OOP: $156; 95% CI $87-$225; p < 0.001 and total: $184; 95% CI $50-$318; p = 0.007). Women also paid > $50 OOP for office-based visits (p < 0.001) and > $55 total expenditures for home healthcare (p = 0.041) compared to men after adjustments. Conclusions Our findings show women with diabetes have higher OOP and total direct expenditures compared to men. Additional research is needed to investigate this disparity between men and women and to understand the associated drivers and clinical implications. Policy recommendations are warranted to minimize the higher burden of costs for women with diabetes.